The sound of the cloud making sense of social and streaming media in the musicianship, marketing, and communication of a young, emerging musician - Marcojos, Rhomel Isaac Barredo
This study focuses on how young, emerging musicians make sense of social and streaming media platforms in the context of their musicianship, self-marketing, and communications. Additionally, it gives light to how music trends, social and streaming media algorithms, and content data might influence or even contribute to the innovation of these areas of being a musician, which allows the effects of social media culture and digital algorithms' determinism on young, emerging artists to be studied and analyzed.